Clinico-histological correlation in Hansen's disease: Three-year experience at a newly established tertiary care center in central India - Shruti Semwal; Deepti Joshi; Garima Goel; Dinesh Asati; Neelkamal Kapoor (Wolters Kluwer Medknow Publications, 2018)
Background: Hansen's disease is a chronic infectious disease caused by Mycobacterium leprae. It is characterized by a wide range of clinical and histological manifestations. Ridley-Jopling criteria are widely used for classifying leprosy. The demonstration of acid-fast bacilli on slit-skin smear examination and in skin biopsy aids in its diagnosis. Aim: The aim of the present study was to perform clinico-histological correlation of skin lesions in all patients with a clinical suspicion of Hansen's disease. Materials and Methods: The study included skin biopsies of all suspected cases of Hansen's disease received over a period of 3 years. Hematoxylin and eosin and Fite-Faraco stained sections of all cases were examined. Corresponding slit-skin smears, if available, were also reviewed. Results: During the study, a total of 116 cases were clinically diagnosed as Hansen's disease. Clinico-histological correlation was obtained in 62.9% of the cases (73/116). The most common histological subtype of Hansen's disease was borderline tuberculoid (TT) (40/116). Seven cases were diagnosed as lepromatous leprosy, five as TT, four as histoid, one as indeterminate, and three cases diagnosed as erythema nodosum leprosum. Fite-Faraco stain was positive in 33/73 cases. Out of 116 cases, slit-skin smears were available for 43 cases and were positive in 23 cases. Conclusion: Correlation between clinical, bacteriological, and morphological features is required for accurate classification of Hansen's disease. Clinical detection and morphological diagnosis of early lesions remain challenging, and the histological findings should always be interpreted in correlation with clinical findings.